Phenolic compound from Mallotus barbatus (Wall.) Muell. - Arg. (Euphorbiaceae). - Trang, Vu Minh; Huong, Le Thu; Trang, Phan Minh; Song, Phan Tong (Vietnam Journal of Chemistry, 2012)
From the leaves of Mallotus barbatus (Wall.) Muell. -Arg. (Euphorbiaceae) six phenolic compounds, methyl gallate, gallic acid, protocatechuic acid, quercetin, kaempferol, and kaempferol 3-O-β-D-glucopyranoside, and three triterpenoid/steroid compounds, taraxerol, β-sitosterol, and β-sitosterol 3-O-β-D-glucopyranoside were isolated. Their chemical structures were determined by spectroscopic analyses.